HUBUNGAN ASUPAN ZAT BESI, VITAMIN C DAN TEMBAGA DENGAN KADAR HEMOGLOBIN PADA MAHASISWA ANGKATAN 2014 FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Elvicha Nurman Savitri; Fatmawati "; Erwin Christianto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Anemia in teenagers is mostly caused by low intake of nutrients, required for hemoglobin formation, that are iron (Fe), vitamin C and copper. Iron is needed to form heme part of hemoglobin, vitamin C is essential for hemoglobin formation and copper is required for iron absorption in the gastrointestinal tract. This study analytically conducted with cross-sectional study approach. Dietary iron, vitamin C and copper intakes were assessed using semi-quantitative Food Frequency Questioner (FFQ) forms, then daily consumption mean was assessed and processed using Nutrisurvey programme. Hemoglobin levels was measured by spectrophotometry using cyanmethemoglobin method. Samples of this study are 80 students that fulfilled the inclusion criteria. This study showed that 62,5% samples who had low intake of iron had hemoglobin levels of 52,5% normal, 10% anemia and 0% polycythemia. Around 53,75% samples that had low vitamin C intake had hemoglobin levels of 7,5% anemia, 46,25% normal and 0% polycythemia. Around 81,25% samples that had high copper intake had hemoglobin levels of 11,25% anemia, 70% normal and 0% polycythemia. In general, there is no significant correlation (p>0,05) between dietary iron, vitamin C and copper intakes towards hemoglobin levels in students class of 2014 at Faculty of Medicine, University of Riau.Key words: Iron intake, vitamin C, copper, hemoglobin levels